2015
DOI: 10.1590/0100-83582015000200009
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate Effectiveness in the Control of Macrophytes Under a Greenhouse Condition

Abstract: -The aim of this study was to assess the effectiveness of glyphosate, as Rodeo ® formulation, to control Eichhornia crassipes, Pistia stratiotes, Salvinia molesta, Salvinia herzogii and Urochloa subquadripara, under greenhouse conditions. The doses assessed were (480, 960, 1440, 1920, 2400, 2880, 3360 and 3840 g ha ) displayed 100% effectiveness for all four macrophyte species. Under greenhouse conditions, the glyphosate in formulation Rodeo ® with 0.5% of Aterbarne ® BR surfactant showed excellent effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 8 publications
1
6
0
4
Order By: Relevance
“…Doses dos herbicidas testadas nos experimentos de controle de U. subquadripara. A melhor eficácia (1440 g ha -1 ) foi similar ao ocorrido em condições semelhantes de estudo com 100% de controle desta mesma planta com a aplicação de 2880 g ha -1 de glyphosate, na formulação Rodeo  + 0,5% de adjuvante Aterbane BR  na calda (Cruz et al, 2015b).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Doses dos herbicidas testadas nos experimentos de controle de U. subquadripara. A melhor eficácia (1440 g ha -1 ) foi similar ao ocorrido em condições semelhantes de estudo com 100% de controle desta mesma planta com a aplicação de 2880 g ha -1 de glyphosate, na formulação Rodeo  + 0,5% de adjuvante Aterbane BR  na calda (Cruz et al, 2015b).…”
Section: Resultsunclassified
“…No experimento 1 (Tabela 2) a dose de 240 g ha -1 glyphosate isolado apresentou o máximo de 95% de controle entre 21 e 60 DAA com as plantas com os caules com coloração verdes e algumas folhas ainda presentes similar ao 42 e 84 g ha -1 de saflufenacil + glyphosate (240 e 480 g ha -1 ), com o máximo de 90% de controle aos 60 DAA (Tabela 3). Estas doses de saflufenacil acrescidas de 720 g ha -1 promoveram 100% de controle da U. subquadripara (Tabela 3), sendo mais efetivas do que o glyphosate na formulação Rodeo  com controle desta mesma planta com 2880 g i.a ha -1 (Cruz et al, 2015b) e do glyphosate 3360 e 4320 g ha -1 para a U. subquadripara e U. mutica (Carbonari et al, 2003), enquanto que, para Brachiaria decumbens a mistura de 1080 g i.a de glyphosate + 24,5 g ha -1 de saflufenacil apresentou 99,3% de controle em 14 DAA (Queiroz et al, 2014).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…The effectiveness of some herbicides -such as imazapyr (Sellers et al, 2008); triclopyr and 2,4-D in mesocosm condition (Wersal et al, 2010); fluridone (Cheshier et al, 2011); endothal in mesocosm condition (Poovey et al, 2013); penoxsulam (Christopher, 2013); imazamox (Christopher, 2013); diquat (Christopher, 2013) and glyphosate (Sellers et al, 2008;Cruz et al, 2015) -has been demonstrated in many studies.…”
Section: Introductionmentioning
confidence: 99%
“…Its action mechanism is given by the inhibition of the EPSPs enzyme (5 enolpyruvylshikimate-3-phosphate synthase), which catalyzes the reactions of aromatic amino acid synthesis in plants, fungi and bacteria (Rodrigues and Almeida, 2011;Palaro et al, 2013). The evaluation of this molecule in controlling the macrophytes: Salvinia molesta (Nelson et al, 2001;Fairchild et al, 2002), Urochloa mutica (Chaudhari et al, 2012), Alternanthera phyloxeroides, Eichhornia crassipes, Pistia stratiotes, Ludwigia grandiflora, Myriophyllum aquaticum e S. molesta (Emerine et al, 2010), E. crassipes (Campos et al, 2013) e E. crassipes, P. stratiotes, S. molesta, S. herzogii and U. subquadripara (Cruz et al, 2015) has been described by various authors in controlled condition.…”
Section: Introductionmentioning
confidence: 99%